A retrospective analysis to determine if exercise training-induced thermoregulatory adaptations are mediated by increased fitness or heat acclimation - Ravanelli, N.; Gagnon, D.; Imbeault, P.; Jay, O. (Experimental Physiology, 2021)
New Findings " What is the central question of this study? Are fitness-related improvements in thermoregulatory responses during uncompensable heat stress mediated by aerobic capacity or is it the partial heat acclimation associated with training? " What is the main finding and its importance? During uncompensable heat stress, individuals with high and low displayed similar sweating and core temperature responses whereas exercise training in previously untrained individuals resulted in a greater sweat rate and a smaller rise in core temperature. These observations suggest that it is training, not per se, that mediates thermoregulatory improvements during uncompensable heat stress. Abstract It remains unclear whether aerobic fitness, as defined by the maximum rate of oxygen consumption , independently improves heat dissipation in uncompensable environments, or whether the thermoregulatory adaptations associated with heat acclimation are due to repeated bouts of exercise-induced heat stress during regular aerobic training. The present analysis sought to determine if independently influences thermoregulatory sweating, maximum skin wettedness (Omega max) and the change in rectal temperature (DeltaTre) during 60 min of exercise in an uncompensable environment (37.0 ± 0.8°C, 4.0 ± 0.2 kPa, 64 ± 3% relative humidity) at a fixed rate of heat production per unit mass (6 W kg-1). Retrospective analyses were performed on 22 participants (3 groups), aerobically unfit (UF; n = 7; : 41.7 ± 9.4 ml kg-1 min-1), aerobically fit (F; n = 7; : 55.6 ± 4.3 ml kg-1 min-1; P < 0.01) and aerobically unfit (n = 8) individuals, before (pre; : 45.8 ± 11.6 ml kg-1 min-1) and after (post; : 52.0 ± 11.1 ml kg-1 min-1; P < 0.001) an 8-week training intervention. Omega max was similar between UF (0.74 ± 0.09) and F (0.78 ± 0.08, P = 0.22). However, Omega max was greater post- (0.84 ± 0.08) compared to pre- (0.72 ± 0.06, P = 0.02) training. During exercise, mean local sweat rate (forearm and upper-back) was greater post? (1.24 ± 0.20 mg cm-2 min-1) compared to pre- (1.04 ± 0.25 mg cm-2 min-1, P < 0.01) training, but similar between UF (0.94 ± 0.31 mg cm-2 min-1, P = 0.90) and F (1.02 ± 0.30 mg cm-2 min-1). The Delta Tre at 60 min of exercise was greater pre- (1.13 ± 0.16°C, P < 0.01) compared to post- (0.96 ± 0.14°C) training, but similar between UF (0.85 ± 0.29°C, P = 0.22) and F (0.95 ± 0.22°C). Taken together, aerobic training, not per se, confers an increased Omega max, greater sweat rate, and smaller rise in core temperature during uncompensable heat stress in fit individuals.